2019
DOI: 10.1186/s12876-019-1039-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost-comparison analysis of FIB-4, ELF and fibroscan in community pathways for non-alcoholic fatty liver disease

Abstract: Background The identification of patients with advanced liver fibrosis secondary to non-alcoholic fatty liver disease (NAFLD) remains challenging. Using non-invasive liver fibrosis tests (NILT) in primary care may permit earlier detection of patients with clinically significant disease for specialist review, and reduce unnecessary referral of patients with mild disease. We constructed an analytical model to assess the clinical and cost differentials of such strategies. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 53 publications
2
89
0
Order By: Relevance
“…A further two articles were identified through supplementary searches of grey literature. As such, a total of 19 articles [11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (capturing 16 different models) were included in the review; summary details of identified studies are shown in Table 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further two articles were identified through supplementary searches of grey literature. As such, a total of 19 articles [11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (capturing 16 different models) were included in the review; summary details of identified studies are shown in Table 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…A total of 13 articles assessed health economic outcomes associated with different screening or diagnostic strategies [16,[18][19][20][21][26][27][28][29][30][31][32][33]; five assessed outcomes with different treatments, including lifestyle intervention, pioglitazone, vitamin E and obeticholic acid as well as bariatric surgery for overweight/obese patients with NASH [17,[22][23][24][25]. The remaining article examined the overall clinical and economic burden of disease and as such was a non-comparative study [11].…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Therefore, diagnostic decisions should be made individually based on the specific case, the available diagnostic tools and the potential harms and benefits of the different diagnostic tools. Table 1 shows an overview of the advantages and disadvantages of available diagnostic tools (49).…”
Section: Diagnosticsmentioning
confidence: 99%
“…7 An improvement in referral practices and noninvasive tests has increased the rate of early detection of asymptomatic chronic liver diseases. 68 This paradigm change opens up the opportunity for mechanism-based therapies to halt disease progression during earlier (i.e., prefibrotic) phases of the disease progression. Fig.…”
Section: Before Fibrosismentioning
confidence: 99%